Mirror Therapy in Increasing Muscle Strength in Stroke Patients - Mardiana Mochamad Ramdan; Fitri Nurlina (HealthCare Nursing Journal, 2024)
A stroke is a pretty serious health disorder when not treated immediately. A common problem is hemiparesis, where the patient will have difficulty performing daily activities, such as walking, working, eating, drinking, and so on. Mirror Therapy is one of the rehabilitation therapies with the help of mirrors that can be done in patients with hemiparesis. This therapy can be claimed to increase muscle strength in hemiparesis. The purpose of this writing is to analyze the application of mirror therapy to increased muscle strength in stroke patients. The method used is systematic review with search engines elsivier, PubMed, and Proquest. The keywords used are mirror therapy, stroke, and muscle strength. The SLR process step uses PRISMA and produces 8 articles for analysis. The results of the study have been obtained that, the effect of the application of mirror therapy to increase muscle strength, results is a significant difference in motor skills before and after the therapy, this application is effective when performed for 15–30 minutes every 3 times in a week, for 1-2 months or 12-20x exercise in 1-2 months. Mirror therapy can be applied to all stroke patients whether ischemic or hemorrhagic without visual impairment. Therefore, it is expected that mirror therapy can be performed in hospitals or home care as a patient rehabilitation program.